Idiopathic Ileo-Ileo-Cecal Intussuception in a 25-Year-Old Female - Zaghrine, Elie (Am J Case Rep, 2019)
Patient: Female, 25 Final Diagnosis: Leo-ileo-cecal intussuception Symptoms: Abdominal pain Medication: — Clinical Procedure: — Specialty: Surgery OBJECTIVE: Rare disease BACKGROUND: Intussusception is defined as the penetration or telescoping of a segment of bowel into a more distal segment. Intussusception is a common cause of small bowel obstruction, especially in children. However, this finding is much less common in adults. Furthermore, when present in adults, intussusception is often found in association with some sort of organic mass, such as a tumor or pancreatic divisum that acts as a lead point, dragging the proximal segment into the distal one. The presence of an intussusception in an adult patient with no obvious lead point is very uncommon. CASE REPORT: Here we report a case of ileo-ileo-cecal double intussusception in an adult patient that yielded no lead point on surgical exploration. The patient was a 25-year-old female who presented with symptoms of obstruction and was diagnosed with the intussusception via computed tomography scan. Surgical resection of the bowel was necessary as reduction could not be accomplished. CONCLUSIONS: The finding of intussusception in an adult patient is far less common than in children, and even more rare when a lead point is not established. When surgery is required, a thorough exploration should be performed to search any signs of a potential lead point. Laparoscopy is usually preferred to laparotomy; however, in this case the degree of distention determined the surgical approach. Thus, due to severe distention, laparotomy was preferred.